Rectus Capitis Posterior Minor: Histological and Biomechanical Links to the Spinal Dura Mater. Issue 8 (15th April 2017) - Venne, Gabriel; Rasquinha, Brian J.; Kunz, Manuela; Ellis, Randy E.
Abstract : Study Design: Serial histological investigation was performed on 10 cadaveric specimens and biomechanical tests were performed on five specimens, both focused on the tissue connexion between the rectus capitis posterior minor (RCPMi) and the spinal dura. Objective: This study had two components: to clarify the microscopic structure of the tissue link between RCPMi and the dura mater, and to evaluate the mechanical role of this tissue complex. Summary of Background Data: Dissection-based and imaging-based reports have suggested a connective tissue link between the RCPMi and the dura mater at the posterior-atlanto-occipital (PAO) level. Existence of this link, and properties, remain unclear. Methods: Histological investigation: RCPMi muscles, their bony attachments, PAO space, and adjacent spinal dura mater were resected from 10 cadavers. Tissues were subdivided into medial and lateral parts. Serial histological sections were prepared to cover maximum surface area; Masson trichrome stain was used to evaluate the tissue connection. Biomechanical investigation: individualized RCPMi muscles from five cadavers were detached from their origin. Each muscle was loaded incrementally up to 2 kg, with the cervical spine hyperextended. Using a structured light scanner, the dura mater was scanned for each loaded state. Comparison between unloaded and each loaded scanned surface quantified the displacement of the dura mater. Results: Histological investigation confirmed the existence of a connective tissue link between the RCPMi and the dura mater. The biomechanical testing suggests that this tissue link complex can reduce the bulging of the dura mater into the spinal canal, caused during hyperextension, by 53.4% ± 6.9% under RCPMi loading. Conclusion: This histological investigation clarified the structure of the tissue link between the RCPMi and the dura mater. The biomechanical testing indicated a potential mechanical function of the RCPMi in regards to the spinal dura mater, which may include a stabilizing role of the dura mater during neck extension. Level of Evidence: N/A